An estimate of plant biomass and assessment of the ecological balance capacity of the Hanoi green corridor - Hoàng, Đình Việt (2020)
The Green Corridor (GC) is a new concept of the Master planning of Hanoi to 2030, vision 2050. The role of the GC is to become an urban logistics area to preserve the landscape and ensure urban living environment. In particular, balancing urban living environment is a very esential goal. The GC accounts for 68% of Hanoi's natural land. The tree land in the GC is the ideal carbon sink to assist the city reduce the nagative impact of Urban Heat Island (UHI), CO2 balance in the air. However, under the pressure of urbanization and the existence of urban, industrial development projects and other ongoing activities . The area of trees in the Hanoi’s GC has been declining rapidly, which reduces the ability to absorb CO2 that human activities discharge. By applied the concept of plant biomass. This thesis provides an approach through quantifying carbon contained in vegetation in the GC and the ability to balance CO2 in the air of GC. Combined with remote sensing images, which is currently the strongly tool to apply for estimating biomass in large scale and complex terrain like Hanoi city.